Time-frequency domain characteristics analysis of a hydro-turbine governor system considering vortex rope excitation. (January 2022) - Lei, Liuwei; Li, Feng; Xu, Beibei; Egusquiza, Mònica; Luo, Xingqi; Zhang, Junzhi; Egusquiza, Eduard; Chen, Diyi; Jiang, Wei; Patelli, Edoardo
Abstract: Understanding and simulating the dynamic characteristics of the hydro-turbine governor system is essential to guarantee the safety of the hydro-power systems. This study proposes a modification method of the water head at the draft tube inlet, which is to discretize the draft tube and introduce the excitation term of the vortex rope. The proposed approach is applied for the modeling of the hydro-turbine governor system. The proposed model (Model I) is verified by means of a comparison with a second model (Model II) of the hydro-turbine governor system model without considering the vortex rope and verified against the experimental data during the load reduction. The model developed is accurate providing errors of the water head, inlet water head and flow of the hydro-turbine for Model Ⅰ are within ±3.3%, ±2% and ±5%, respectively. The proposed model overcomes the limitations of Model Ⅱ in the time-domain and frequency-domain since that only provides the average pressure at the draft tube, which do not reflect the pressure fluctuation and energy fluctuation. Instead the proposed model allows to capture and model the energy fluctuation during the load reduction as shown in the experimental results. The proposed model promotes the development of the hydro-turbine governor system model. Highlights: A hydro-turbine governor system model is established, considering the vortex rope excitation. The characteristics of the proposed model are analyzed in the time and frequency domain. The proposed model is suitable for the actual situation by comparing with the experimental results. This study provides the theoretical basis for studying the stable operation of hydropower stations.